Penyutradaraan Program Acara “Berkah Islami” di Kompas TV Jawa Tengah - Muhammad Aufar Al Wafi; yanuar Luqman (Interaksi Online, 2020)
Television is one of the mainstream media which is still become the most consumed media by the society for getting information and entertainment. Because there are still a lot of audiences, so the copetition among the programs are growing as well. Berkah Islami appear in the middle of society to present Islamic Religious program which is easy to watch and easy to listen. The topics that will be discussed are about adab and sunnah which is very related to our daily life. This program will be packed up in different way. In the first segmen it will be a news feature, and then in the second one it will be a talk show, and the last one it’s gonna be an illustrasion sketch comedy. In this program, “Berkah Islami”, the director is leading a whole production process, from the pre production until the post production. The director is also in charge to explore the creative ideas to wrapped up the program to be interesting and make it happen, so “Berkah Islami” is finally created. Berkah Islami aired on Kompas TV Jawa Tengah every Sunday at 05.00 WIB, started since 1st September to 24th Noveber 2019. With this program, I hope the society get an alternative Islamic Religious TV Program and also educate and become a reminder for the society abaout adab and sunnah in our daily live at once.